Питание дикой свиньи (Sus scrofa L.) в Украинских Карпатах - Гунчак, Н.С. (Вестник зоологии, 1980)
Species composition of the Sus scrofa food in the Carpathians is represented by 54 species of herbaceous plants, 17 species of wood-shrub plants and 10 species of farm crops. Winter is the hardest season for Sus scrofa in the Carpathians, because the absence of food leads to death of many animals, especially of young ones. Proper distribution of food fields and feeding sites will help to reduce to minimum the harm caused by Sus scrofa and to prevent them from dying in winter.